2013
DOI: 10.1371/journal.pone.0055976
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Conscious and Unconscious Conflict Adaptation

Abstract: Recently, researchers have been trying to unravel the function of consciousness by exploring whether unconscious information is (in)capable of exerting cognitive control. Theoretically, cognitive control functions, such as conflict adaptation, have often been assumed to require consciousness. However, empirical evidence on conscious versus unconscious conflict adaptation is highly contradictory and hitherto, only one study reliably demonstrated adaptation to unconscious conflict. Therefore, the current study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
52
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 44 publications
(63 reference statements)
9
52
1
Order By: Relevance
“…In 1957, market researcher James Vicary infamously claimed that tachistoscopic presentations of "eat popcorn" and "drink Coca Cola" during screenings of the movie Picnic increased sales of both products, but his claims were bogus (Pratkanis, 1992). Despite that initial stumble, evidence of unconscious priming is now firmly established (e.g., Dehaene et al, 1998), though specific effects are still occasionally attributed to conscious perception or awareness (e.g., Desender, Van Lierde, & Van den Bussche, 2013). Coming full circle, Vicary's claim has recently been substantiated: Subliminal primes can affect drink brand choice if participants are thirsty enough (Karremans, Stroebe, & Claus, 2006).…”
Section: Masked Primingmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1957, market researcher James Vicary infamously claimed that tachistoscopic presentations of "eat popcorn" and "drink Coca Cola" during screenings of the movie Picnic increased sales of both products, but his claims were bogus (Pratkanis, 1992). Despite that initial stumble, evidence of unconscious priming is now firmly established (e.g., Dehaene et al, 1998), though specific effects are still occasionally attributed to conscious perception or awareness (e.g., Desender, Van Lierde, & Van den Bussche, 2013). Coming full circle, Vicary's claim has recently been substantiated: Subliminal primes can affect drink brand choice if participants are thirsty enough (Karremans, Stroebe, & Claus, 2006).…”
Section: Masked Primingmentioning
confidence: 99%
“…Fortunately, even if our account is incorrect, it is proved to be useful in helping motivate the investigation of an important new phenomenon, namely the adaptive modulation of masked priming by variations in prime context. We are pleased to note that whether such adaptive modulations reflect "smart" or "dumb" mechanisms are currently an active area of research (e.g., Desender et al, 2013).…”
Section: Accounting For These Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have now demonstrated that unconscious primes cannot only be processed at the perceptual and motor levels (e.g., Dehaene et al, 2004;Dehaene et al, 2001;Eimer & Schlaghecken, 2003), but also afford high-level processing, such as semantic (Van den Bussche, Notebaert, & Reynvoet, 2009) or emotional processing (Naccache et al, 2005). More important to note, recent studies also demonstrated that conflict adaptation may be triggered by unconscious stimuli (Desender, Van Lierde, & Van den Bussche, 2013;Francken, Gaal, & de Lange, 2011;van Gaal, Lamme, & Ridderinkhof, 2010). It is generally assumed that high-level cognitive functions subtended by prefrontal cortex such as cognitive control can only be elicited consciously (Dehaene & Changeux, 2011).…”
mentioning
confidence: 99%
“…Most studies reporting unconscious conflict adaptation have used a 2 ϫ 2 stimuli/response mapping (Desender et al, 2013;van Gaal et al, 2010; but see Kunde, 2003), whereas studies in which adaptation was restricted to conscious primes typically used larger stimulus sets (e.g., Ansorge et al, 2011;Frings & Wentura, 2008;Greenwald, Draine, & Abrams, 1996). If this difference is of crucial importance, it might be the case that only the overall conflict is susceptible to unconsciously triggering adaptation, whereas the more specific types may not be.…”
mentioning
confidence: 99%